PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL PADA PEMERINTAH KABUPATEN/KOTA PROVINSI SUMATERA SELATAN PERIODE 2017-2021 - Manurung, Seprita; Sembiring, Sabeth (UNIKA Santo Thomas, 2024)
This study aims to determine the effect of Regional Original Income and General Allocation Funds on Capital Expenditures in the Regencies/Cities Government of South Sumatra Province for a period 2017-2021. The sample of this study is the entire population consisting of 17 districts/cities with a 5 year study period. The research method used is quantitative using secondary data sourced from the APBD Realization Report obtained from the website of the Directorate General of Fiscal Balance of the Republic of Indonesia. The analysis technique used is descriptive statistical analysis then classical assumption testing and finally hypothesis testing. Partially it shows that Regional Original Income has a positive and significant effect on Capital Expenditure. The General Allocation Funds have no effect on Capital Expenditure. Simultaneous it shows that Local Own Revenue and General Allocation Fund have a positive and significant effect on Capital Expenditure.